A human infection with a novel reassortant H3N2 swine virus in China. Issue 2 (August 2019) - Lu, Jing; Yi, Lina; Jing, Yi; Tan, Hanqing; Mai, Wei; Song, Yingchao; Zou, Lirong; Liang, Lijun; Xiao, Hong; Kang, Min; Wu, Jie; Song, Tie; et al.
Highlights: Retrospective surveillance on ILI samples identifies a S-OIV H3N2 (A/GD/277/H3N2/2017) which caused a spill-over infection in a young child. Hemagglutination-inhibition test shows A/GD/277/H3N2/2017 is antigenically distinct from seasonal H3N2 viruses currently circulating in the human population. A/GD/277/H3N2/2017 is a novel reassortant of EA-H1N1 and H3N2 previously circulating in swine in southern china. Phylogenetic analysis shows A/GD/277/H3N2/2017-like virus caused another spill-over infection in Vietnam in 2010 suggesting the firm establishment of this swine lineage in Southeast Asia.